Penerapan Metode TOPSIS Untuk Pemberian Bantuan Bedah Rumah Di Nagari Lunang Selatan - Fitriyani, Intan Nur; Defit, Sarjon; Nurcahyo, Gunadi Widi (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Indonesian government seeks to improve people's welfare by holding various poverty reduction programs, one of which is providing assistance to uninhabitable houses (RTLH). Equitable development of the welfare of Indonesian society must be comprehensive and even, starting from the smallest scope, namely the village. One of the villages in Indonesia that has implemented a program to provide assistance for uninhabitable houses is Nagari Lunang Selatan which is located in Lunang sub-district, Pesisir Selatan Regency, West Sumatra Province. The implementation of the uninhabitable housing assistance program in Nagari Lunang Selatan has so far still used a manual system so it is not effective because the final results are not objective. There are 5 criteria and 10 alternatives as sample data used in this research. These criteria include the number of dependents, total expenses, total income, land ownership status, and condition of the house. For this reason, this research provides a solution by implementing a decision support system for providing assistance for uninhabitable housing using the Technique For Order of Preference by Similarity to Ideal Solution method, known as TOPSIS, the TOPSIS method is suitable for solving semi-structural problems such as the problem of providing assistance for inadequate housing. inhabit. The aim of this research is to produce a system that can facilitate decision making regarding providing assistance for uninhabitable housing. The results obtained from the test calculation process on sample data of 10 alternatives with 5 criteria provide accurate results. From this test, the results obtained for 3 alternatives as recipients of house renovation assistance